2011
DOI: 10.1007/s10549-011-1663-3
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of breast cancer susceptibility loci with patient characteristics, metastasis-free survival, and mRNA expression of the nearest genes

Abstract: To understand the biology of low-risk breast cancer alleles, and to investigate whether these loci also contribute to disease progression that was once established, we examined the association of SNPs tagging the low-risk breast cancer loci in or near FGFR2, LSP1, MAP3K1, H19, TOX3, POU5F1P1, MYC, and 2q35, with clinical, pathological characteristics, prognosis, and mRNA expression of the nearest genes. Tumor DNA samples of 2,480 breast cancer patients were available. Out of this cohort, 1,290 patients with ly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 26 publications
(38 reference statements)
3
39
0
Order By: Relevance
“…In the cis- analysis, we observed 3 transcripts associated with 3 risk loci at an FDR<0.1 (2q35/ IGFBP5 , 5q11/ C5orf35 , and 16q12/ TOX3 ). Interestingly, the association with TOX3 (in the same direction) has been previously observed further demonstrating the utility of publicly available data (Riaz et al, 2012). IGFBP5 is a strong candidate gene for mediating the effect of the 2q35 risk locus.…”
Section: Discussionsupporting
confidence: 69%
“…In the cis- analysis, we observed 3 transcripts associated with 3 risk loci at an FDR<0.1 (2q35/ IGFBP5 , 5q11/ C5orf35 , and 16q12/ TOX3 ). Interestingly, the association with TOX3 (in the same direction) has been previously observed further demonstrating the utility of publicly available data (Riaz et al, 2012). IGFBP5 is a strong candidate gene for mediating the effect of the 2q35 risk locus.…”
Section: Discussionsupporting
confidence: 69%
“…CITED1 is a transcription coregulator that enhances the activity of transcription factors such as ERs (Yahata et al, 2001). A correlation between the rs3803662 genotype and decreased TNRC9 mRNA has been observed in breast tumors, in which transcription of this gene decreases in an allele-dependent manner (Riaz et al, 2012). To date, one study has shown an effect of TNRC9 expression on BC, showing that increased levels of TNRC9 mRNA predict bone metastasis in this disease (Smid et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Many of the risk SNPs map to non-protein-coding regions and are thought to influence transcriptional regulation (Hindorff et al 2009;Freedman et al 2011). In some instances the proximity of the SNP to a plausible candidate gene has provided a potential mechanism (Meyer et al 2008;Riaz et al 2012;Bojesen et al 2013), but several of the breast cancer risk SNPs map to gene deserts with the nearest known gene mapping several hundred kilobases (kb) away.…”
mentioning
confidence: 99%